FORMATION OF NATIONAL CONSCIOUSNESS THE YOUNG GENERATION BY MEANS STUDY OF RITUALS AND TRADITIONS OF THE UKRAINIAN PEOPLE - M.V. Viktorova (Academy of Cognitive and Natural Sciences, 2022)
The article investigates the problem of transmitting generally accepted cultural values of the Ukrainian people and the specific character of its national word view. These two grounds are of primary importance and make an essential basis for upbringing personal qualities of a Ukrainian citizen for the further development of the national education.